Misconceptions About Buffer Solutions - Idha Ayu Kusumaningrum; Marantika Lia Kristyasari (Journal of Educational Chemistry (JEC), 2022)
There are many misconceptions in the chemistry discussion that can influence students to acquire new knowledge, one of which is regarding buffer solutions. It is one of the chemical concepts consisting of abstract ideas which likely trigger students' misconceptions. However, research on this topic was still limited. Thus, in the present study, researchers attempted to diagnose students' misconceptions about buffer solutions by administering a two-tier multiple-choice test. Research data were analyzed qualitatively and quantitatively. Respondents in this study were 98 second-semester eleventh-grade students majoring in Science in 3 senior high schools, with high (A), moderate (B), and poor (C) categories based on the 2015 National Examination's scores. The misconceptions detected were about what buffers do, what buffers are, and how buffers can do what they do. These findings were discovered in schools with a moderate category.